Descriptive analysis of the secondary school teachers' classroom teaching techniques - Masilungan, Juanita C. (1970)
The aim of the study is to describe the patterns of teacher behavior, the principles underlying teaching activities and other aspects of classroom teaching in the Philippine public secondary schools in an effort to find ways of improving teacher-preparation in our teacher training institutions. Through the study, teacher training institutions will be provided with baseline data on what the curriculum needs to be in terms of teaching strategies in the pre-service education program.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Teaching